Dynamic Modeling of Time Cost Trade Off in Design and Build Projects of High Rise Office Buildings - Husin, Albert Eddy; Danumurti, Alwan (Universitas Ibn Khaldun Bogor, 2023)
This paper aims to determine the impact of accelerated duration on profit and contingency costs. The method uses the design and build project of a high-rise office building, which begins with an analysis of the actual project schedule, the possibility of accelerating the duration with the assumption of additional working hours for workers and the impact of perceived duration on project costs. Then proceed with System Dynamic (SD) modeling with reference to the Time Cost Trade Off theory and end with a scenario of the relationship between project activity acceleration, profit addition and crashing costs. Project acceleration can improve project performance by considering the effect on profits and contingency costs, with a Schedule Performance Index (SPI) of up to 37.8%, it can increase profits between 4.08% due to reduced indirect costs.